The Evolution of Same-Sex Attraction - Apostolou, Menelaos. author. (orcid)0000-0002-0685-1848 Link aut Link
XVIII, 250 p.
Keywords: This book provides a comprehensive analysis of the evolutionary origins of same-sex attraction, evaluating multiple existing evolutionary theories. It combines empirical findings with theoretical arguments in order to review evidence on the prevalence rates of same-sex attraction and determine its genetic and environmental basis. Among the topics addressed: Attitudes towards same-sex attraction across human history Assessing the weak selection pressures hypothesis of attraction Assessing the male choice hypothesis of attraction Evolution of same-sex attraction in men versus women The Evolution of Same-Sex Attraction will be of interest to academics and students of evolutionary and psychological sciences, filling a gap in literature on the origins of specifically same-sex attraction. .